Sistem Layanan Sirkulasi di Perpustakaan SMK Tamansiswa Padang - Purwanti, Ardella; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
The purpose of this study is to describe: (1) The circulation service system which use by SMK Tamansiswa Padang’s library, (2)The obstacle which faced by librarian at SMK Tamansiswa. Data were collected through observation and interviews with staff librarian at SMK Padang Tamansiswa. Analyzing the data can be describe. The study's findings are circulation services at SMK PadangTamansiswa using an open service system (open access system), the problems encountered in service at the library circulation Tamansiswa SMK Padang is on (1) laboris not background librarians with library science so less able to carry out their duties, (2) The library userless motivated to visit the library so teachers make classroom learning in the library.Keywords: library service; circulation